Effect of silver-coated silica nanoparticles on the thermal conductivity of thermally activated acrylic resin - Silva, Juliana de Freitas Gouveia [UNESP]; Rossi, Natália Rivoli [UNESP]; de Menezes, Beatriz Rossi Canuto; Thim, Gilmar Patrocinio; Paes Junior, Tarcísio José de Arruda [UNESP] (Editora Cubo, 2022)
Objective: Thermally activated acrylic resins (RAATs) are widely used in dentures as a base material due to their good dimensional stability and biocompatibility. However, their low thermal conductivity is a disadvantage, as it affects acceptance when using dental prostheses. Thus, the objective of this work was to measure the conduction heat in RAATs with and without incorporation of silica and silver nanoparticles (NP) and rigid reline (RR). Material and Methods: For this, samples were made and divided into 10 groups (n = 6). The first five groups were 2-mm-thick samples: G1 (RAAT control), G2 (RAAT + RR control), G3 (RAAT and NP + RR), G4 (RAAT + RR and NP), and G5 (RAAT and RR modified by NP). In the other five groups, 8-mm-thick samples were made: G6 (RAAT control), G7 (RAAT + RR control), G8 (RAAT and NP + RR), G9 (RAAT + RR and NP), and G10 (RAAT and RR modified by NP). The heat that cross the surface of the specimens was quantified using a wireless device. The data were submitted to two-factor ANOVA statistical analysis and Tukey´s test with a 5% significance level. Results: After measuring the temperature variation as a function of time, it can be observed that there was a statistically significant difference for thermal conduction between the control groups and those modified with NP. Conclusion: Thus, it was possible to conclude that the NP improved the heat conduction in RAAT and in the RR because the nanoparticles have a higher thermal conductivity.
Efeito das nanopartículas de sílica revestidas por prata na condutividade térmica da resina acrílica ativada termicamente
Keywords: Acrylic resin; Nanoparticle; Silver; Thermal conductivity